2016
DOI: 10.1590/1982-02752016000300008
|View full text |Cite
|
Sign up to set email alerts
|

Personality and aggression: A contribution of the General Aggression Model

Abstract: The aim of the study was to identify the direct and indirect existing relationship among personality traits on aggression of high school and undergraduate students from the city of João Pessoa, Brazil, using the General Aggression Model as the theoretical framework. The sample consisted of 218 students, of which 107 were high school students and 111 undergraduate students. The instruments used for data collection were as follows: Aggression Questionnaire, the Big Five Inventory and a Socio-Demographic Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
1
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 32 publications
4
14
1
19
Order By: Relevance
“…In both cultures, we found that increased positivity to vengeance was associated with lower agreeableness and higher neuroticism, as found in previous studies (McCullough et al, 2001;McCullough & Hoyt, 2002). Low agreeableness is related to aggressiveness, emphatic deficits, and difficulties developing close relationships and selfishness -all characteristics that can accentuate a willingness to take revenge (Cavalcanti & Pimentel, 2016;Ruggi et al, 2012). High neuroticism predisposes people to more intensely experience negative emotions, such as anger, and to ruminate about negative events, which may elicit strong negative emotions and reactions towards a transgressor (Barber, Maltby, & Macaskill, 2005;McCullough & Hoyt, 2002).…”
Section: Correlations With Personalitysupporting
confidence: 87%
“…In both cultures, we found that increased positivity to vengeance was associated with lower agreeableness and higher neuroticism, as found in previous studies (McCullough et al, 2001;McCullough & Hoyt, 2002). Low agreeableness is related to aggressiveness, emphatic deficits, and difficulties developing close relationships and selfishness -all characteristics that can accentuate a willingness to take revenge (Cavalcanti & Pimentel, 2016;Ruggi et al, 2012). High neuroticism predisposes people to more intensely experience negative emotions, such as anger, and to ruminate about negative events, which may elicit strong negative emotions and reactions towards a transgressor (Barber, Maltby, & Macaskill, 2005;McCullough & Hoyt, 2002).…”
Section: Correlations With Personalitysupporting
confidence: 87%
“…Τα ευρήματα αυτά συνάδουν με το ΓΜΕ (βλ. επίσης Barlett & Anderson, 2012· Cavalcanti & Pimentel, 2016. Ωστόσο, μέσω της παρούσας ανα-σκόπησης αναδείχτηκαν επίσης ορισμένες διαδραστικές σχέσεις, οι οποίες δεν λαμβάνονται υπόψη από το συγκεκριμένο θεωρητικό πλαίσιο (π.χ.…”
Section: συμπεράσματαunclassified
“…Ωστόσο, σε αρκετές περιπτώσεις η υπάρ-χουσα βιβλιογραφία επικεντρώνεται στη μελέτη άμεσων σχέσεων συγκεκριμένων παραγό-ντων και μηχανισμών με τη συμμετοχή σε περιστατικά εκφοβισμού/θυματοποίησης και όχι στις αλληλεπιδραστικές σχέσεις πολλαπλών μεταβλητών (Ettekal et al, 2015). Εντούτοις, δεν είναι λίγες οι έρευνες στον διεθνή και ελληνικό χώρο που έχουν στραφεί στη μελέτη διαδρα-στικών σχέσεων μεταξύ ατομικών, καταστασιακών παραγόντων και ενδιάμεσων μηχανι-σμών/διαδικασιών, που μπορεί να συμβάλλουν στην εκδήλωση ΠΕ/ΚΕ και ΠΘ/ΚΘ (Andreou & Metallidou, 2004· Barlett & Anderson, 2012· Cavalcanti & Pimentel, 2016· Kokkinos, Karagianni et al, 2016· Kokkinos, Voulgaridou, Mandrali, & Parousidou, 2016 · · Papadaki & Giovazolias, 2015 · Smack, Kushner, & Tackett, 2015). Συνεπώς, η παρούσα ανασκόπηση συνθέτει και παρουσιάζει κριτικά ερευνητικά ευ-ρήματα που αφορούν τόσο άμεσες όσο και έμμεσες σχέσεις παραγόντων και διαδικασιών που συνδέονται με τα εν λόγω φαινόμενα.…”
unclassified
“…According to this model, media content (e.g., violent or prosocial video game) affects the processing of new information by activating at least one of three routes: cognitions, arousal, and affect. This process results in cognitions (positive or negative thoughts), which in turn results in behaviours (Anderson & Bushman 2002;Anderson & Dill, 2000;Cavalcanti & Pimentel, 2016;DeWall, Anderson, & Bushman, 2011;Greitemeyer & Osswald, 2009;Tear & Nielsen, 2013).…”
Section: Introductionmentioning
confidence: 99%